Improvement in Cerebral and Ocular Hemodynamics Early after Carotid Endarterectomy in Patients of Severe Carotid Artery Stenosis with or without Contralateral Carotid Occlusion. (23rd August 2016) - Wang, Jian; Wang, Weici; Jin, Bi; Zhang, Yanrong; Xu, Ping; Xiang, Feixiang; Zheng, Yi; Chen, Juan; Sheng, Shi; Ouyang, Chenxi; Li, Yiqing
Abstract : Purpose . To investigate the alternation in cerebral and ocular blood flow velocity (BFV) in patients of carotid stenosis (CS) with or without contralateral carotid occlusion (CO) early after carotid endarterectomy (CEA). Patients and Methods . Nineteen patients underwent CEA for ≥50% CS. Fourteen patients had the unilateral CS, and five patients had the ipsilateral CS and the contralateral CO. Transcranial Doppler (TCD) and Color Doppler Imaging (CDI) were performed before and early after CEA. Results . In patients with unilateral CS, significant improvements in BFV were observed in anterior cerebral artery (ACA) and middle cerebral artery (MCA) on the ipsilateral side after CEA. In patients of ipsilateral CS and contralateral CO, significant improvements in BFV were observed in the ACA and MCA not only on the ipsilateral side but also on the contralateral side postoperatively. The ipsilateral ophthalmic artery (OA) retrograde flows in two patients were recovered to anterograde direction following CEA. The BFV in short posterior ciliary artery (SPCA) of the ipsilateral side significantly increased postoperatively irrespective of the presence of contralateral CO. Conclusions . CEA improved cerebral anterior circulation hemodynamics especially in patients of unilateral CS and contralateral CO, normalized the OA reverse flow, and increased the blood perfusion of SPCA.